Fresh State, Rheological and Microstructural Characteristics of Alkali-Activated Mortars Developed Using Novel Dry Mixing Technique under Ambient Conditions - Dhruv Sood; Khandaker M. A. Hossain (Applied Sciences, 2021)
Ambient cured alkali-activated mortars (AAMs) are developed through the activation of supplementary cementitious materials (SCMs) by powder form reagents with silica sand using a novel dry-mixing method. The fresh state, rheological, compressive strength and microstructural characteristics of eight AAM mixes are comprehensively investigated. The effects of binary/ternary combinations/proportions of SCMs, different combinations/dosages of powder form reagents and the fundamental chemical ratios (SiO2/Al2O3, Na2O/SiO2, CaO/SiO2 and Na2O/Al2O3) present in the precursors and the reagents are investigated. The AAM mixes obtained compressive strengths ranging from 34 to 42.6 MPa with initial and final setting times between 122 and 458 min and 215 and 483 min, respectively. The yield stress and viscosity of the mixes decreased with the increase in the slump flow spread. All the mixes demonstrated pseudoplastic behavior. The microstructural analysis revealed the formation of more longer polymeric chains comprising Si-Al linkages in N-C-A-S-H/N-A-S-H gels for reagent one (calcium hydroxide:sodium metasilicate = 1:2.5) mixes, which resulted in a lower slump flow, higher yield stress, higher plastic viscosity and quicker setting times compared to their reagent two (calcium hydroxide:sodium sulfate = 2.5:1) counterparts.